Association between Family Functioning, Domestic Violence and Parent-Child Relation and the Attitude of being Victims of Bullying among High School Girls - Fahimeh Pourmand; Farshad Mohsenzadeh; Ali Ghaedniay-jahromi (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objectives: Becoming a victim of bullying at school is one of the compatibility problems during adolescence. Bullying could be in form of physical, sexual and psychological harassment from one or more students repeatedly over a period of time. Various factors could inflence shaping this behavior or becoming its victim. The objective of this study was to investigate the role of family functioning, domestic violence, and parent-child relationship in being a bullying victim among high school girls. Material and Methods: This cross-sectional descriptive study was conducted in 2015. The sampling framework included all the female high school students from district seven of Tehran. As many as 383 individuals were randomly selected by using the staged- cluster sampling method. Olweus bully/victim questionnaire, straus domestic violence questionnaire, parent-child relationship scale, and family assessment device were used for data collection for the study. IBM SPSS statistics 18 was employed in performing the statistical analysis. Results: Being victim of bullying was meaningfully correlated with family functioning (r=0.58, P=0.005), domestic violence (violence of father: (r=0.67, P=0.003) and violence of mother: (r=0.43, P=0.007) and parent-child relationship (r=-0.54, P=0.006), Physical aggression of fathers (P<0.001), their positive emotion (P<0.001), and problem solving (P=0.001) directly, and mother's functionality disorder/confusion (P<0.001), father's anger (P=0.001), and mother's physical aggression (P=0.002) reversely predicted being victim. Conclusion: The study showed that the family directly and indirectly affects becoming a victim of bullying. Parent-child relationship forms adolescent behavior patterns. Therefore, training parents in appropriate child raising methods could play an important role in preventing much social harm in the future.